Research on the Linkage between RMB Interest Rate and Exchange Rate - Huang, Tianqi (International Journal of Global Economics and Management, 2024)
This study uses a vector autoregressive (VAR) model to investigate the relationship between the exchange rate (EX) and RMB interest rate (I). The research starts with a review of pertinent theoretical frameworks and then conducts an empirical analysis with historical data to determine the long-term interactions between these two macroeconomic factors in the Chinese market. The empirical findings demonstrate the extent to which the I affects EX as well as the reciprocal relationship between EX and I The stability of the linkage is further explored using variance decomposition and impulse response analysis. In addition to offering policymakers a foundation for regulating monetary policy, this study offers a fresh viewpoint on the macroeconomic dynamics of China.